Selfing ability and drift load evolve with range expansion. Issue 5 (29th August 2019) - Koski, Matthew H.; Layman, Nathan C.; Prior, Carly J.; Busch, Jeremiah W.; Galloway, Laura F.
Abstract: Colonization at expanding range edges often involves few founders, reducing effective population size. This process can promote the evolution of self‐fertilization, but implicating historical processes as drivers of trait evolution is often difficult and requires an explicit model of biogeographic history. In plants, contemporary limits to outcrossing are often invoked as evolutionary drivers of self‐fertilization, but historical expansions may shape mating system diversity, with leading‐edge populations evolving elevated selfing ability. In a widespread plant, Campanula americana, we identified a glacial refugium in the southern Appalachian Mountains from spatial patterns of genetic drift among 24 populations. Populations farther from this refugium have smaller effective sizes and fewer rare alleles. They also displayed elevated heterosis in among‐population crosses, reflecting the accumulation of deleterious mutations during range expansion. Although populations with elevated heterosis had reduced segregating mutation load, the magnitude of inbreeding depression lacked geographic pattern. The ability to self‐fertilize was strongly positively correlated with the distance from the refugium and mutation accumulation—a pattern that contrasts sharply with contemporary mate and pollinator limitation. In this and other species, diversity in sexual systems may reflect the legacy of evolution in small, colonizing populations, with little or no relation to the ecology of modern populations.